2017
DOI: 10.1097/prs.0000000000003687
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Psychosocial Function of Children with Craniofacial Anomalies

Abstract: Risk, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Children with orofacial cleft suffer the highest incidence of depression, anxiety, and negative peer-relationships around the ages 8 to 10 years. 33 This supports a tiered-approach with psychosocial support, counselling, and surgery used together within a multidisciplinary cleft and craniofacial team.…”
Section: Intermediate Cleft Rhinoplastymentioning
confidence: 61%
“…Children with orofacial cleft suffer the highest incidence of depression, anxiety, and negative peer-relationships around the ages 8 to 10 years. 33 This supports a tiered-approach with psychosocial support, counselling, and surgery used together within a multidisciplinary cleft and craniofacial team.…”
Section: Intermediate Cleft Rhinoplastymentioning
confidence: 61%
“…Grade III: Absent auricle, the lobular remnant is anteriorly and inferiorly displaced [14]. (8) Dysmorphic type of skull shows a spherical big head with a medium-width nostrils, rounded orbital edges, prominent cheekbones, shallow canine fossae, moderate prognathism, absent brow ridges, giant skull sutures, prominent zygomatic bones, wide and flat nasal bridge, less prominent nasal spine, shovelshaped upper incisor teeth (scooped out behind), moderately wide palate shape, arched sagittal contour, wide, and flat face [15,16] The congenital defects affect 2-3% of all children and about 1% of them have syndromes or multiple deformities [1]. Syndromes consist of multiple malformations that could be etiologically or pathogenetically related or both.…”
Section: Introductionmentioning
confidence: 99%
“…CFA might be associated with diverse genetic and environmental factors. There is a significant psychological impact of altered facial and dental appearance in patients with craniofacial anomalies compared to controls [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of psychosocial ramifications, we and others have reported that significant psychosocial disturbances occur specifically in children with craniofacial anomalies between 8 and 10 years of age including increased anxiety, depression, poor peer relationships, obsessive-compulsive behavior, and aggression. 10 , 11 For these reasons, many surgeons will aim to perform reconstruction between ages 6 and 8 years.…”
Section: Introductionmentioning
confidence: 99%